2021
DOI: 10.36590/jika.v3i2.157
|View full text |Cite
|
Sign up to set email alerts
|

Pola Konsumsi Berisiko dan Sosio-Demografi Sebagai Faktor Resiko Penyakit Hipertensi

Abstract: Hipertensi merupakan penyakit ketiga terbesar di Kecamatan Aek Kuasan. Tingginya kejadian hipertensi ini bisa disebabkan banyak faktor seperti halnya sosio-demografi dan pola konsumsi beresiko. Tujuan studi ini untuk mengetahui determinan kejadian hipertensi berdasarkan faktor sosio-demografi dan pola konsumsi beresiko. Studi ini menggunakan metode deskriptif analik dengan desain studi Cross-sectional yang dilaksanakan pada Juli-Agustus 2021 di Desa Aek Loba Afdeling 1. Didapatkan Total responden sebanyak 184 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several studies have shown that factors that can increase blood pressure include excessive salt consumption. In addition, frequent consumption of preserved foods has also been shown to have a significant relationship with the incidence of hypertension (Insani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that factors that can increase blood pressure include excessive salt consumption. In addition, frequent consumption of preserved foods has also been shown to have a significant relationship with the incidence of hypertension (Insani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%